Management of Severe Trismus with Bilateral Recurrent Pericoronitis alongwith Chronic Oral Submucous Fibrosis - A Case Report - Nanda Kishore Ghoshal, (Journal of Orofacial Research, 2021)
A 37 years, old male patient reported with the chief complaint of inability to open mouth since 10-11 months and recently painand swelling resulting from wisdom teeth of both sides limited the mouth opening severely (15mm after 3 weeks, >22mm after 6 weeks,>27mm after 9 weeks).